PENGELOLAAN LIMBAH B3 MEDIS RUMAH SAKIT DI SUMATERA BARAT PADA MASA PANDEMI COVID-19 - Elsa Yolarita; Desi Widia Kusuma (Puslitbang Upaya Kesehatan Masyarakat, 2020)
ABSTRACT The problem of managing medical waste is still an obstacle for most hospitals, especially during the COVID-19 pandemic. This study aims to determine the amount ofmedical waste, evaluation of hospital medical waste management and the implementation of discretion in West Sumatera during COVID-19 pandemic. Data collection was carried out by distributing questionnaires online with google forms. The results showed that the amount of medical waste almost doubled during the pandemic, with the largest being around 41,670 kg month. Management that does not comply with standards is storage of medical waste, selecting a special route, transportation by special trolly, disinfection and non-compliance with the use of PPE for waste officers. Discretion was carried out by 4 hospitals with obstacles including the incinerator not meeting the requirements and the absence of medical waste transportation. It is recommended that the hospital conduct monitoring and evaluation of medical waste management and compliance with the use of PPE for waste officers. The local government facilitates discretion through the procurement of medical waste transportation to PT. Semen Padang, strive for large hospitals to process medical waste from surrounding health care facilities and build a medical waste transfer depot. Keywords: Hospital, medical waste, COVID-19, discretion ABSTRAK Persoalan pengelolaan limbah B3 medis masih menjadi kendala sebagian besar rumah sakit terutama pada masa pandemi COVID-19. Penelitian ini bertujuan mengetahui jumlah limbah B3 medis, evaluasi pengelolaan limbah B3 medis rumah sakit serta pelaksanaan diskresi di Sumatera Barat pada masa pandemi COVID-19. Pengumpulan data dilakukan melalui penyebaran kuesioner secara daring dengan google forms. Hasil penelitian menunjukkan jumlah limbah B3 medis rata-rata meningkat hampir 2 kali lipat pada masa pandemi, terbesar sekitar 41.670 kg/bulan. Pengelolaan yang tidak sesuai standar adalah pengurangan dan pemilahan, penyimpanan limbah B3 medis, pemilihan jalur khusus,pengangkutan dengan trolly khusus, disinfeksi serta ketidakpatuhan penggunaan Alat Pelindung Diri (APD) petugas limbah. Diskresi dilaksanakan oleh 4 rumah sakit dengan kendala antara lain incinerator tidak memenuhi persyaratan dan ketiadaan transportasi limbah B3 medis. Disarankan rumah sakit untuk melakukan monitoring dan evaluasi pengelolaan limbah B3 medis serta kepatuhan penggunaan APD petugas limbah. Pemda memfasilitasi diskresi melalui pengadaan transportasi limbah B3 medis ke PT. Semen Padang, mengupayakan rumah sakit besar mengolah limbah B3 medis dari Fasyankes sekitarnya dan membangun transfer depo limbah B3 medis. Kata kunci: Rumah sakit, limbah B3 medis, COVID-19, diskresi